Artificial intelligence in solving dermatological problems - Viktor Shpudeiko; Kirill Sokolov; Hanna Sidaruk (Termedia Publishing House, 2023)
Skin diseases remains a significant medical problem. It is associated with increasing prevalence, morbidity, and relapses, as well as development of complications, which has a negative impact on the patient's quality of life. The approach to the diagnosis and treatment of dermatological diseases has changed significantly with the development of information technology. Algorithms of artificial intelligence are developed to assist dermatologists with the diagnosis of diseases. They may facilitate early diagnosis and reduce the number of appointments, reduce the waiting time for specialist consultations and the correct distribution of patient referrals to doctors of other specialties. This article focuses on this developing field of knowledge. Key words: skin, recognition, dermatology, assistant, neural network.